Novel cationic radical acceptors for visible light-mediated reactions - Filippini, Dario (2023)
The addition of carbon-centered radicals to alkenes is a cornerstone process in organic chemistry, which has triggered significant advances in various areas of synthesis. Despite its value, the chemistry often requires specific substitution in either the radical trap or the carbon-centred radical to ensure controllable and efficient reactivity, overall limiting the scope of application of the chemistry. The aim of the research presented in the following thesis dissertation is to challenge these limitations, exploring the use of vinyl phosphonium and sulfonium ions as radical acceptors in photoredox catalysis. The use of such reagents allowed us to significantly extend the scope of application of classic radical addition to alkenes, opening new avenues in radical chemistry. In Chapter 2 and 3, the radical reactivity of vinyl phosphonium ions is exploited to develop a novel C-C coupling technology to functionalise carboxylic acid and alcohol substrates. The chemistry hinges on merging radical chemistry with the Wittig reaction and was demonstrated to be suitable for the late-stage functionalisation of complex substrates. In Chapter 4 and 5, vinyl sulfonium ions are shown to undergo radical conjugate addition under photoredox conditions. The chemistry was exploited to develop a formal polarity mismatched radical addition upon coupling with nucleophiles and allowed to develop a novel methodology to access oxetanes from aliphatic alcohols.